2016
DOI: 10.1038/srep22927
|View full text |Cite
|
Sign up to set email alerts
|

Local control on precipitation in a fully coupled climate-hydrology model

Abstract: The ability to simulate regional precipitation realistically by climate models is essential to understand and adapt to climate change. Due to the complexity of associated processes, particularly at unresolved temporal and spatial scales this continues to be a major challenge. As a result, climate simulations of precipitation often exhibit substantial biases that affect the reliability of future projections. Here we demonstrate how a regional climate model (RCM) coupled to a distributed hydrological catchment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 46 publications
1
41
0
1
Order By: Relevance
“…Several coupled atmospheric‐hydrological modeling studies have shown the potential role of surface and subsurface lateral water flow on precipitation (e.g., Anyah et al, ; Arnault et al, ; Larsen, Christensen, et al, , Larsen, HĂžjmark Rasmussen, et al, ; Maxwell et al, ; Rahman et al, ; Senatore et al, ; Wagner et al, ). Indeed, lateral terrestrial water flow redistributes soil moisture, which then potentially affects surface fluxes, atmospheric boundary layer condition, and finally precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several coupled atmospheric‐hydrological modeling studies have shown the potential role of surface and subsurface lateral water flow on precipitation (e.g., Anyah et al, ; Arnault et al, ; Larsen, Christensen, et al, , Larsen, HĂžjmark Rasmussen, et al, ; Maxwell et al, ; Rahman et al, ; Senatore et al, ; Wagner et al, ). Indeed, lateral terrestrial water flow redistributes soil moisture, which then potentially affects surface fluxes, atmospheric boundary layer condition, and finally precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Corsmeier et al () further described convective initiation as a two‐way interaction from larger and longer scales (e.g., upper tropospheric processes) down to smaller and shorter scales (e.g., boundary layer and soil‐surface driven processes) and vice versa. Larsen, Christensen, et al () showed that an enhanced treatment of subsurface hydrological processes in a climate model, for example, 3‐D groundwater flow, potentially improves the representation of seasonal precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The southern regions in the blues and purples are grouped toward the right and middle section of the figure (deeper groundwater tables with positive LE difference). The influence of water table depth on latent heat fluxes across the land surface has been previously noted by Maxwell and Kollet (); Larsen et al ().…”
Section: Model Demonstrationmentioning
confidence: 99%
“…Recent studies showed that considering the horizontal transport of terrestrial water in a climate model has an impact on precipitation (e.g., Arnault, Wagner, et al, ; Arnault et al, ; Kerandi et al, ; Larsen et al, ; Maxwell et al, ; Rahman et al, ; Rummler et al, ; Senatore et al, ; Wagner et al, ; Zhang et al ). Indeed, spatially redistributing soil moisture modifies surface fluxes, which potentially affects boundary layer dynamics, convection initiation and precipitation (e.g., Pielke, ).…”
Section: Introductionmentioning
confidence: 99%